Terminal device and wireless data transmission network - CRESCINI, MATTEO (2005)
A terminal device (10) for measuring at least one physiological parameter on a subject and radiotransmitting the value of the measured parameter to a central processor, comprising a housing including therein an electronic control card (11) comprising a radio frequency transceiver (1) and an analogue/digital converter (2) connected thereto, an antenna (16) connected to the transceiver (1), an acceleration sensor (12) connected to the electronic card (11), an on/off switch (15) connected to the electronic card (11), and a connector (13), connected to the electronic card (11), suitable to be connected to at least one external sensor of a physiological parameter.